Optimalisasi Sumber Daya Manusia terhadap Pengolahan: Studi Kasus Industri Pengolahan Bahan Baku Rotan - Herry Christopher Tene; Pratono, Aluisius Hery; Tanaya, Olivia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Rattan is a non-wood raw material originating from Indonesia which has become the main source of income for community forests and local governments. Rattan processing has challenges in obtaining raw materials and skilled processing techniques by workers or human resources in order to produce quality output which of course can also advance the company. The use of machines and human resources in the rattan production process can increase production speed and accuracy. This research was conducted to determine the performance of human resources which influences the quality of the rattan products produced. The research method used in this research is a type of qualitative research with a descriptive approach and has an exploratory nature. The data collection technique in the research was carried out by creating an inductive scheme to make it easier for researchers to carry out research analysis and based on existing case studies. Observations were carried out by researchers regarding activities that occurred in the company during the researcher's internship period. The research object of rattan processing and human resources is information from the UD company. Alam Sultra's work. The research results show that the company UD. Karya Alam Sultra carries out empowerment by providing skills and training to its workers to improve the quality of employee performance in processing rattan so that it can become good quality rattan. This proves that there is empowerment in the processing of rattan raw materials, enabling the performance skills of human resources to increase efficiency and innovation in the processing of rattan products and produce quality rattan.